1998
DOI: 10.1021/jm980043e
|View full text |Cite
|
Sign up to set email alerts
|

Styrylquinoline Derivatives:  A New Class of Potent HIV-1 Integrase Inhibitors That Block HIV-1 Replication in CEM Cells

Abstract: On the basis of the fact that several polynucleotidyl transferases, related to HIV integrase, contain in their active site two divalent metal cations, separated by ca. 4 A, new potential HIV integrase inhibitors were designed, in which a quinoline substructure is linked to an aryl nucleus possessing various hydroxy substitution patterns, by means of an ethylenic spacer. Although the most active compounds contain the catechol structure, this group is not essential for the activity, since compound 21 that lacks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
153
1
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(160 citation statements)
references
References 58 publications
2
153
1
4
Order By: Relevance
“…The compounds were screened for their inhibitory activity in a 3Ј-processing assay which was performed as described previously. 3,10) Effects against the strand transfer activity were evaluated during the same assay from the homologous integration events and found to be no significant differences from 3Ј-processing inhibition, thus confirming that coumarins affect equally both steps of the integration reaction. Table 1 lists the inhibitory activity of a series of mono-or bis-hydroxylated benzoyl biscoumarins against the recombinant wild-type HIV-1 IN enzyme.…”
Section: Resultsmentioning
confidence: 79%
“…The compounds were screened for their inhibitory activity in a 3Ј-processing assay which was performed as described previously. 3,10) Effects against the strand transfer activity were evaluated during the same assay from the homologous integration events and found to be no significant differences from 3Ј-processing inhibition, thus confirming that coumarins affect equally both steps of the integration reaction. Table 1 lists the inhibitory activity of a series of mono-or bis-hydroxylated benzoyl biscoumarins against the recombinant wild-type HIV-1 IN enzyme.…”
Section: Resultsmentioning
confidence: 79%
“…20,21) Effects against the strand transfer activity were evaluated during the same assay from the homologous integration events and found to be no significantly different from 3Ј-processing inhibition, thus confirming that coumarins affect equally both steps of the integration reaction. Table 1 lists the inhibitory activity of a series of bis-or tetra-coumarin analogues against the recombinant wild-type HIV-1 IN enzyme.…”
Section: Chemistrymentioning
confidence: 85%
“…Recently, it has also been shown that in case of quinoline derivatives the presence of the catechol structure with free hydroxyl groups is not essential for activity but it may be replaced by a carboxyl or a cyano group (Mekouar et al, 1998). Furthermore, the presence of a carboxyl group has been shown to decrease the cytotoxicity of some derivatives (Mekouar et al, 1998).…”
Section: Discussionmentioning
confidence: 99%